2018
DOI: 10.1111/cge.13368
|View full text |Cite
|
Sign up to set email alerts
|

Further audiovestibular characterization of DFNB77, caused by deleterious variants in LOXHD1, and investigation into the involvement of Fuchs corneal dystrophy

Abstract: This study focuses on further characterization of the audiovestibular phenotype and on genotype-phenotype correlations of DFNB77, an autosomal recessive type of hearing impairment (HI). DFNB77 is associated with disease-causing variants in LOXHD1, and is genetically and phenotypically highly heterogeneous. Heterozygous deleterious missense variants in LOXHD1 have been associated with late-onset Fuchs corneal dystrophy (FCD). However, up to now screening for FCD of heterozygous carriers in DFNB77 families has n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…However, in the four families we have studied, all the patients and the family members with normal hearing but carrying a single heterozygous mutation in the LOXHD1 gene showed no corneal abnormalities. Other studies also reported no symptoms of FCD were observed in the probands and their blood-related relatives [7,10,33]. Although the relationship of LOXHD1-related hearing loss and FCD is still unclear, we suggest that ophthalmologic examinations should be performed in patients with ARNSHL when LOXHD1 is suspected to be the pathogenic gene.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, in the four families we have studied, all the patients and the family members with normal hearing but carrying a single heterozygous mutation in the LOXHD1 gene showed no corneal abnormalities. Other studies also reported no symptoms of FCD were observed in the probands and their blood-related relatives [7,10,33]. Although the relationship of LOXHD1-related hearing loss and FCD is still unclear, we suggest that ophthalmologic examinations should be performed in patients with ARNSHL when LOXHD1 is suspected to be the pathogenic gene.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, studies suggested that a single heterozygous mutation of LOXHD1 was also associated with another hereditary disease, Fuchs corneal dystrophy (FCD) [9]. Other studies demonstrated conflicting conclusions that there was no association between LOXHD1 mutations and FCD [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A murine study has demonstrated that the first damaged part of cochlear hair cells was the stereocilia in the basal cochlear turn, which respond to the highest frequencies [5], indicating low frequencies should have relative milder damage. A milder HL was also reported in some patients with LOXHD1 variants [5] [8]. However, studies reported that some LOXHD1 variants are associated with a more severe HL [23] [18] [9] [19].…”
Section: Discussionmentioning
confidence: 99%
“…To date, about 100 cases with DFNB77 have been reported [8] [9] [10] [11] [5]. However, the acoustic characteristics are heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…They show different auditory characteristics and audiometric phenotypes, varying from mild to profound and from stable to progressive sensorineural HL. 5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Animal c.5869G>T Nonsense Het Moderate-severe Non-progressive Japanese 3 5 c.4480C>T Nonsense Het Moderate-severe Non-progressive Japanese 4 7 c.884C>T Missense Het Moderate-severe Progressive -5 7 c.2825_2827delAGA Frameshift Het Moderate-severe Progressive -6 7 c.2797C>T Nonsense Het Profound Non-progressive -7 7 c.1730T>G Frameshift Het Profound Non-progressive -8 7 c.2722G>A Missense Het Profound Non-progressive -9 7 c. 13 However, Wesdorp et al 4 found that the type of variant (nonsense or missense) did not associate with HL severity, and that the combination of a nonsense and missense variant could cause different audiometric phenotypes. Such research is limited, so correlations between LOXHD1 variants and phenotypic characteristics of HL remain unclear.…”
Section: Discussionmentioning
confidence: 99%